Inter-epidemic abundance and distribution of potential mosquito vectors for Rift Valley fever virus in Ngorongoro district, Tanzania - Clement N. Mweya; Sharadhuli I. Kimera; Lesakit S. B. Mellau; Leonard E. G. Mboera (Taylor & Francis Group, 2015)
Background: Rift Valley fever (RVF) is a mosquito-borne viral zoonosis that primarily affects ruminants but also has the capacity to infect humans. Objective: To determine the abundance and distribution of mosquito vectors in relation to their potential role in the virus transmission and maintenance in disease epidemic areas of Ngorongoro district in northern Tanzania. Methods: A cross-sectional entomological investigation was carried out before the suspected RVF outbreak in October 2012. Mosquitoes were sampled both outdoors and indoors using the Centre for Disease Control (CDC) light traps and Mosquito Magnets baited with attractants. Outdoor traps were placed in proximity with breeding sites and under canopy in banana plantations close to the sleeping places of animals. Results: A total of 1,823 mosquitoes were collected, of which 87% (N=1,588) were Culex pipiens complex, 12% (N=226) Aedes aegypti, and 0.5% (N=9) Anopheles species. About two-thirds (67%; N=1,095) of C. pipiens complex and nearly 100% (N=225) of A. aegypti were trapped outdoors using Mosquito Magnets. All Anopheles species were trapped indoors using CDC light traps. There were variations in abundance of C. pipiens complex and A. aegypti among different ecological and vegetation habitats. Over three quarters (78%) of C. pipiens complex and most (85%) of the A. aegypti were trapped in banana and maize farms. Both C. pipiens complex and A. aegypti were more abundant in proximity with cattle and in semi-arid thorn bushes and lower Afro-montane. The highest number of mosquitoes was recorded in villages that were most affected during the RVF epidemic of 2007. Of the tested 150 pools of C. pipiens complex and 45 pools of A. aegypti, none was infected with RVF virus. Conclusions: These results provide insights into unique habitat characterisation relating to mosquito abundances and distribution in RVF epidemic-prone areas of Ngorongoro district in northern Tanzania.